Pengembangan Perangkat Lunak Generate File Data Kehadiran Pegawai Universitas Palangka Raya: Development of Software Generate Recording File Attendance Data of Universitas Palangka Raya - Putra, Putu Bagus Adidyana Anugrah; Pranatawijaya, Viktor Handrianus; Widiatry, Widiatry; Sari, Nova Noor Kamala (Anterior Jurnal, 2019)
Science and technology are experiencing very rapid development, one of them in the field of web applications whose growth has been increasing rapidly. Staffing Department of Universitas Palangka Raya has used applications to manage employee data, one of them is the employee attendance list. However, the management is still not efficient because staff from the staffing department cannot directly enter employee attendance status such as leave, permission, and illness directly on attendance data processors because they have to wait for data retrieval from the electronic attendance machine at the end of the month so that the process of making attendance recapitulation runs slowly. Software development in generating a file of the attendance data of Universitas Palangka Raya employees using the Waterfall software development method. The first step is to carry out a needs analysis of the system created, including library research, data collection, consultation, and design. Based on this analysis, the system design was created that uses Data Flow Diagrams, and Entity Relationship Diagrams, as the system design that will be created. The next step is writing the program code. In writing program code, the programming languages used are HTML, CSS, and JavaScript as interface designs supported by PHP and MySQL programming languages for data storage and exchange. In the next step, testing is done to test the functionality of the application that has been made using the black box method. This software will be a tool to generate files on attendance data for Universitas Palangka Raya employees.